ANÁLISE DE AUMENTO MÉDIO DO NÍVEL DO MAR NA BACIA HIDROGRÁFICA DO ITAQUI, SÃO LUIS-MA: USO DO MODELO EXPERIMENTAL BR MANGUE - CARVALHO, Ana Carolina Coutinho (2024)
This research addresses the impacts of climate change on the Itaqui River Basin, located in São Luís-MA, with an emphasis on sea level rise and the consequences arising from this phenomenon. The BR-Mangue model was used to simulate future sea level rise scenarios, considering the projections established by the Intergovernmental Panel on Climate Change (IPCC) until the year 2100. Five different greenhouse gas emission scenarios were analyzed, each with a projected sea level rise ranging from 0.3 meters to 1.1 meters. The results indicate that sea level rise could have serious impacts on port infrastructure, especially in the Itaqui Port Complex, one of the main infrastructures in the region. In addition, the local ecosystem, composed of mangrove areas and coastal zones, would also be threatened by erosion and saline intrusion processes. Communities living near the basin, many of which depend on port activities and fishing, would also be severely affected, requiring the development of adaptation and mitigation strategies. The methodology used in the research includes a detailed geospatial analysis, which uses Geographic Information System (GIS) tools, combined with modeling based on cellular automata. This approach allows for a dynamic and comprehensive simulation of the possible impacts of sea level rise on the basin. This study offers a significant contribution to understanding the challenges that coastal areas such as the Itaqui Basin face due to climate change. By identifying potential risks and their impacts, the study provides essential support for the implementation of public policies and urban and environmental planning strategies aimed at adapting to and mitigating the effects of climate change.